Study of the Magnetorheological Behavior and Magnetic-Induced Microstructure of Heavy Crude Oils and Ferrofluids Mixtures (2023)
Global energy policies are undergoing a profound reorientation to provide a more secure, sustainable, and affordable system, moving towards net-zero emissions by 2050. Although investment in clean fuels is set to increase significantly in the coming years, parts of the fossil fuel system remain critical to energy security, such as refineries to supply residual users of transportation fuels. In this context, unconventional hydrocarbons have been a major candidate for current and future oil production, since they exist in abundant quantity on Earth’s crust, representing nearly 70% of proven reserves. Accordingly, great attention has been fundamentally directed towards exploring the promising and growing nanotechnology modern era. Against this background, this thesis is framed in the theoretical and experimental study of the inclusion of ferrofluids in the matrix of heavy crude oils with the aim of proving the induction of magnetorheological effects, primarily focused on improving the flow properties of these complex fluids in pipeline transportation applications. Therefore, it has been demonstrated that the integration of nanoparticles plays a fundamental role as adsorbent and smart magnetically controllable agent, effectively modifying the rheological properties of heavy crude oils. Likewise, surface modification of nanoparticles by adsorption of asphaltenes supported the role of this fraction as facilitator in promoting the spontaneous formation of aggregates. The orientation of these aggregates could be manipulated using external magnetic fields to stimulate more favorable flow properties in heavy crude oils. These findings serve as a fundamental theoretical basis for the development of an innovative technological approach aimed at flow assurance of heavy crude oils.